Uji Aktivitas Sediaan Sabun Padat Kombinasi Ekstrak Daun Kemangi (Ocimum Sanctum L.) dan Ekstrak Daun Bandotan (Ageratum Conyzoides Sleberex Steud) terhadap Bakteri Propionibacterium Acnes - Ery Nourika Alfiraza; Desi Sri Rejeki; Nur Inayah (Jurnal Medika Nusantara, 2025)
Solid soap is a preparation used to clean the skin from dirt and bacteria. Basil leaves and bandotan leaves are plants that have secondary metabolites such as alkaloids, flavonoids, tannins, saponins and steroids that have the potential to be antibacterial. This study was to formulate solid soap from ethanol extract of basil leaf and bandotan leaf as an antibacterial, to determine the formulation of solid soap of bandotan leaf extract and basil extract which has the strongest inhibition zone in the bacterium Propionibacterium acnes. This research method is an experimental method by making basil leaf extract and bandotan leaf extract by maceration with 96% alcohol. Solid soap formulations are made with 3 concentration variations, namely formulation 1 basil extract 7.5% and bandotan extract 12.5%, formulation 2 basil extract 10% and bandotan extract 10% and formulation 3 basil extract 12.5% and bandotan extract 7.5%. Then the antibacterial activity of solid soap was tested with Propionibacterium acnes bacteria by the well dilution method. Conclusion The formulation of basil leaf extract and bandotan leaf extract has antibacterial activity, solid soap preparations from basil leaf extract and bandotan leaf extract have met the quality requirements, in formulations 2 and 3 basil leaf extract and bandotan leaf extract have a strong inhibition zone of 6.7 mm. Then the data was analyzed using one way ANOVA.